Acquired partial lipodystrophy: An atypical presentation with therapeutic challenge - Komali Garlapati; Anusha Rembers; Balaji Dara; Mamatha Boringi (Wolters Kluwer Medknow Publications, 2015)
Lipodystrophy is regarded as a functional disturbance of the hypothalamus. Typically, face is the first part to be affected, and its aspect in an advanced case is characteristic: hollowed temples, prominent zygomatic bones, and sunken cheeks. When the patient smiles, numerous wrinkles appear in the cheeks, giving the appearance of premature senility. Here is a report of a rare case of partial lipodystrophy with an atypical presentation which had alarmingly affected the patient's appearance. Our main purpose of presenting this rare case in oral medicine is an attempt to educate oral physicians about lipodystrophy and increase awareness about the presence of subtle forms that may be underdiagnosed.